Modelos de estimativa da radiação atmosférica em função da temperatura, umidade e dos índices radiométricos Kt e Kd para Botucatu - SP - Dal Pai, Enzo [UNESP] (2014)
This work describes estimation models of atmospheric longwave radiation (LW↓) in Botucatu-SP-Brazil, and was divided into three parts. Part 1 discusses models of classic literature estimated as a function of temperature (Ta) and water vapor pressure (ea) for cloudless conditions. Adjustment coefficients were made for 14 models in the literature depending on the local climate of Botucatu. Then it was proposed similar to classical models (LW↓ = f (Ta, ea)) model by means of regression and measured data Botucatu with a high coefficient of determination (R2 = 0.935). The validation of the proposed model used a independent database of model generation was performed by comparing the estimated with the measured value. Statistical indicative MBE and RMSE obtained show that the proposed model results presented the same order of magnitude of the classical models of the literature. Part 2 brings the development of a model for estimating the atmospheric longwave radiation (LW↓) from the short-wave radiation (extraterrestrial (Io), global (G) and diffuse (d)) for all types of sky coverage. Correlated by linear regression, the atmospheric longwave radiation (LW↓) with radiometric ratios Kt (ratio between (G) and (Io)) and Kd (ratio between (d) and (G)), both with high coefficient of determination (R2 = 0.981 between LW↓ and Kt and R2 = 0.963 between LW↓ and Kd). The direct relationship between (LW↓), (G) and (d) on surface was verified after climate and statistical analysis of the three components using a database of 7 years of measurements. In the spring and summer seasons, the values of (LW ↓), (G) and (d) are higher, accompanied by increases in temperature and concentration of clouds and water vapor in the atmosphere. In the autumn and winter seasons, the values of (LW↓), (G) and (d) are smaller, therefore the values of temperature and concentration of clouds and water vapor are also ...